Polyphenols as potential metabolism mechanisms regulators in liver protection and liver cancer prevention. Issue 1 (13th October 2022) - Li, Shuangfeng; Yin, Shuangshuang; Ding, Hui; Shao, Yingying; Zhou, Shiyue; Pu, Weiling; Han, Lifeng; Wang, Tao; Yu, Haiyang
Abstract: Background: Liver cancer is one of the common malignancies. The dysregulation of metabolism is a driver of accelerated tumourigenesis. Metabolic changes are well documented to maintain tumour growth, proliferation and survival. Recently, a variety of polyphenols have been shown to have a crucial role both in liver disease prevention and metabolism regulation. Methods: We conducted a literature search and combined recent data with systematic analysis to comprehensively describe the molecular mechanisms that link polyphenols to metabolic regulation and their contribution in liver protection and liver cancer prevention. Results: Targeting metabolic dysregulation in organisms prevents and resists the development of liver cancer, which has important implications for identifying new therapeutic strategies for the management and treatment of cancer. Polyphenols are a class of complex compounds composed of multiple phenolic hydroxyl groups and are the main active ingredients of many natural plants. They mediate a broad spectrum of biological and pharmacological functions containing complex lipid metabolism, glucose metabolism, iron metabolism, intestinal flora imbalance, as well as the direct interaction of their metabolites with key cell‐signalling proteins. A large number of studies have found that polyphenols affect the metabolism of organisms by interfering with a variety of intracellular signals, thereby protecting the liver and reducing the risk of liver cancer. Conclusion: This review systematically illustrates that various polyphenols, including resveratrol, chlorogenic acid, caffeic acid, dihydromyricetin, quercetin, catechins, curcumin, etc., improve metabolic disorders through direct or indirect pathways to protect the liver and fight liver cancer. Abstract : Cancer treatment has increasingly relied on drugs of natural origin. Polyphenols are a general term for polyhydroxy compounds synthesized from gallic acid or its polymers of glucitol, flavanols and their derivatives, as well as by mixing the two through the shikimic acid and malonic acid pathways. They are powerful emerging compounds for the prevention and treatment of liver cancer. Most patients with unexplained liver cancer have metabolic syndrome, therefore, regulating metabolism and preventing liver diseases such as NAFLD is one of the effective strategies to prevent liver cancer. Targeting organism metabolism is one of the pathophysiological mechanisms of anticancer drug discovery. This research analyzes that polyphenols improve metabolic disorders through direct or indirect pathways to protect the liver and fight liver cancer.